2020
DOI: 10.1088/1757-899x/924/1/012037
|View full text |Cite
|
Sign up to set email alerts
|

Synthesize & Characterization of Li3PO4(0.5)LiI(0.25)LiCl(0,25) Solid Electrolyte for Lithium Ion Battery

Abstract: Lithium phosphate (Li3PO4) is a promising candidate for solid electrolytes. However its ionic conductivity still stands at 3 × 10−7 S/cm which is very low compared to liquid electrolytes which are contained within widely distributed lithium ion batteries at 10−3 S/cm. This requires a solution to increase its conductivity which is the addition of dopants. The proposed dopants are lithium iodide (LiI) and lithium chloride (LiCl) which is mixed with the Li3PO4, creating the new solid electrolyte system Li3PO4(0.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The Li + conduction inside the interphase highly depends on the conductivity of the components of interphases . For instance, the dominant decomposition products at the Ni90/LPSC interface, Li 2 S and Li 3 PO 4 , have a poor ionic conductivity of 7.51 × 10 –11 and 3 × 10 –7 S/cm, respectively. These undesired interphases will block Li + conduction across the interphase.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The Li + conduction inside the interphase highly depends on the conductivity of the components of interphases . For instance, the dominant decomposition products at the Ni90/LPSC interface, Li 2 S and Li 3 PO 4 , have a poor ionic conductivity of 7.51 × 10 –11 and 3 × 10 –7 S/cm, respectively. These undesired interphases will block Li + conduction across the interphase.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Figure c,d compares Nyquist plots of the Li|LLZT|Li (i.e., uncoated) and Li|LBO|LLZT|Li (i.e., single-side coated) cells. For Li-symmetric cells, it was reported that the main contributors of the impedance can be assigned to the resistances of the bulk electrolyte, grain boundaries, and the Li|electrolyte interface. ,, Therefore, we constructed three RC circuits to represent the EIS fitting curve. The bulk Li-ion conductivities of uncoated and single-side coated cells were determined to be 6.56 × 10 –4 and 4.86 × 10 –4 S/cm, respectively, from the high-frequency semi-circles (1 MHz).…”
Section: Resultsmentioning
confidence: 99%
“…These conductivity values are comparable to the conductivity values (∼10 −4 S/cm) observed by previous studies. 22,34,43 The mid-frequency semi-circles were associated with the grain boundary conductivity, 46,47 which was determined to be 5.2 × 10 −5 S/cm for the uncoated cell and 1.1 × 10 −4 S/cm for the single-side coated cell. The interfacial conductivities were obtained in the lower-frequency ranges (i.e., 10−0.1 Hz) and determined to be 1.32 × 10 −4 S/cm for the uncoated cell and 1.06 × 10 −3 S/cm for the single-side coated cell.…”
Section: ■ Results and Discussionmentioning
confidence: 99%